Clinical Decision Making in Last Semester Senior Baccalaureate Nursing Students - (:unkn) unknown (My University, 2015)
Clinical decision making (CDM) is an integral part of what nurses do (Muir, 2004; Ramezani-Badr, Nasrabadi, Yekta, & Taleghani, 2009). Yet, inspection of the nursing literature reveals concerns about the lack of preparation and readiness of new nursing graduates to engage in effective clinical decision making (Smith & Crawford, 2002, Duchscher, 2008, Gillespie & Paterson, 2009, Benner, Sutphen, Leonard & Day, 2010, Noohi, Karimi-Noghondar, & Haghdoost, 2012). This study was conducted to better understand the nature of students’ decision making and how they learn to make clinical decisions. Nursing students in their final semester of a baccalaureate program participated in this mixed methods study. Data were collected from 168 students at 11 schools in 4 states. Twenty-eight of these students also participated in focus groups. Hammond’s Cognitive Continuum Theory provided the conceptual underpinnings for this study. Two areas of clinical decision making were examined: understanding how senior nursing students learn to make clinical decisions; and determining the nature of the decisions they made. Six themes emerged from the focus group data: Partners in Learning, Finding One’s Voice, Becoming Confident, Multiple Sources of Learning, Patient-Centered Care (The Real Priority), and The Turning Point. These six themes were interrelated, leading to a core concept of Coalescing for Action. In this study, three quarters of the participants scored in the quasi-rational range of clinical decision making, indicating they are flexible making decisions that are dependent on the situation at hand. This contradicts with Benner’s theory (1994) who proposed they remained at the novice/ analytic stage as a student. Based on Hammond’s CCT, the process of growing as a nursing student, through practice and experience requires time and systematic cognitive processing. Students think through the steps of each task they complete. There were no statistically significant relationships between clinical decision making and the predictor variables of age, program type, previous degree/s, previous healthcare experience, or minority status. Having iterative clinical experiences when possible was important to beginning decision makers as it reinforced lessons and solidified concepts. Having opportunities to repeat skills and care for similar patients also increases the cues students receive. As they recognize more cues, they are better positioned to make quicker decisions without having to systematically process everything. Because nursing care is dynamic and unpredictable, some situations have very little cues, regardless of the students (or nurse’s) experience level. Hammond’s CCT makes room for this reality in the quasi-rational mode. The properties of the task lead to the cognition and ultimately, the decision. Regardless of years of experience as a nurse then, decision making is dependent on cognition, the cues recognized, and the task at hand (the familiarity of that task by the nurse). Planning clinical experiences for students in regards to skills and complex patient care situations may greatly enhance decision making abilities. Curricular development with task, cue, and pattern recognition in mind may better prepare students. Creating new models of clinical education that require true partnerships between schools and healthcare agencies may be what are needed to improve students’ entry into the workplace and their readiness for practice. Hiring and preparing clinical instructors who can help students learn to make clinical decisions is essential. Based on these findings, funding for nursing education programs, both undergraduate and graduate education may need enhancement in order to fully prepare students for practice. Limitations include a small sample size, homogeneous focus groups, and the inadvertent omission of gender on the demographic instrument. In addition, only a cross-section of the lives of these nursing students was captured. The results of this study pave the way for future research on nursing student development in clinical decision making in order to provide for a successful entry into the nursing profession. Longitudinal studies throughout nursing school and into practice may better inform clinical decision making abilities. Intervention studies with nursing staff and clinical instructors will allow for new strategies and models to be trialed.
Keywords: Baccalaureate Nursing Students; Clinical Decision Making; Cognition and Critical Thinking; Decision Making; Nursing Students; Undergraduate Nursing Students